2022
DOI: 10.3390/ijms23105575
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Connexin 43 Down Modulation in Human Articular Chondrocytes Stimulated by Tumor Necrosis Factor Alpha

Abstract: Connexin 43 (Cx43) exerts pivotal functions in articular chondrocytes (CH). It is involved in the communication among cells and between cells and the extracellular environment, and it contributes to the maintenance of the correct cell phenotype. The pro-inflammatory cytokine TNFα induces a reduction in Cx43 expression in CH. Here, we studied the dynamics of this decrease in expression. We evaluated Cx43 protein and gene expression and the involvement of C-terminal domain (CTD) cleavage and proteasomal degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…CX43 did not have alternative splicing but had transcriptional factor activity to directly regulate the transcription of N-cadherin [ 37 ]. The protein in the nucleus was shown as two distinct bands [ 38 ], and the expression of N-cadherin was significantly reduced in S-transfected cells. Hence, we suggest another hypothesis that the S reduced the expression of CX43 in the membrane, enhanced CX43 phosphorylation and transfer into the nucleus, and interfered with the structure of the gap junction.…”
Section: Discussionmentioning
confidence: 99%
“…CX43 did not have alternative splicing but had transcriptional factor activity to directly regulate the transcription of N-cadherin [ 37 ]. The protein in the nucleus was shown as two distinct bands [ 38 ], and the expression of N-cadherin was significantly reduced in S-transfected cells. Hence, we suggest another hypothesis that the S reduced the expression of CX43 in the membrane, enhanced CX43 phosphorylation and transfer into the nucleus, and interfered with the structure of the gap junction.…”
Section: Discussionmentioning
confidence: 99%
“…Here, GJA1-20k was proposed to be recruited to the nucleus by basic transcription factor 3 where it forms a complex with polymerase II to regulate N-cadherin transcription ( 127 ) directly implicating a connexin in regulating cellular adhesion at the transcriptional level. Nuclear localization of Cx43 or possibly a C-terminal Cx43 fragment was seen in Wnt-5A– and Wnt-9B–treated cells, whereas TNFα decreased Cx43 nuclear localization prompting the speculation that nuclear Cx43 may be involved in various signaling cascades ( 128 , 129 ). Another study suggests Cx43 is translocated to the nucleus during late G1 phase of the cell cycle by A-kinase anchoring protein 95 ( 130 ).…”
Section: Noncanonical Roles Of Connexins and Connexins Fragmentsmentioning
confidence: 99%
“…[ 20 ] Therefore, blocking Cx43 channels is expected to improve the effectiveness of tumor treatment. [ 21 ] Previous reports have suggested that these Cx43 channels protect tumor cells from ROS damage, thereby facilitating the resistance of tumors to high‐ROS‐mediated therapy. [ 22 ] Given that the innate character of the “bystander effect” of Cx43 in ROS‐mediated tumor catalytic therapy remains controversial, it requires further investigation.…”
Section: Introductionmentioning
confidence: 99%